Cover Picture: Fast Charge and High Stability of Solid‐State Graphite Organic Ionic Plastic Crystal Composite Anodes (Batteries & Supercaps 7/2022). Issue 7 (15th June 2022) - Ueda, Hiroyuki; Mizuno, Fuminori; Kerr, Robert; Forsyth, Maria; Howlett, Patrick C.
Abstract : The Front Cover shows a solid‐state graphite composite anode containing an organic ionic plastic crystal electrolyte as a multifunctional lithium‐ion conductor by which the electrolyte/electrode and electrode/current collector contacts are improved, enabling fast lithiation and stable cycling. More information can be found in the Research Article by H. Ueda, P. C. Howlett and co‐workers .